[Man with mask made in San Juan Nuevo] - Maria Campoverde::::::photographer::: (2005)
Description supplied by photographer: 'Los Curpites estan comiendo en una casa en el barrio de San Mateo. Nosotros estabamos comiendo y el chico de la fota estaba en la otra mesa y yo le pregunte si le podia tomar una foto con su máscara puesta. La máscara que lleva puesta fue hecha a mano por un artesano en San Juan Nuevo.' - 'The Curpite dancers are eating in a home in the barrio of San Mateo. We were eating together and the guy in the photo was at the other table across from me and I asked if I could take a photo of him with his mask on. The mask he is wearing was handmade by an artisan in San Juan Nuevo.'